2003
DOI: 10.1097/00004872-200304000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of evening administration of guanabenz and clonidine on morning hypertension

Abstract: The results suggest that evening administration of the central alpha(2)-agonists guanabenz and clonidine effectively suppresses the morning BP elevation in treated hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…The combination of drug-and gene-based therapies enables simultaneous treatment of all key metabolic syndrome pathologies. Guanabenz (Wytensin) is a clinically licensed antihypertensive drug that is thought to activate alpha-2-selective adrenergic receptors in the central nervous system, thereby reducing the sympathetic outflow to heart, kidney, and peripheral vasculature and decreasing the systolic and diastolic blood pressure (9). Recently, guanabenz was also identified as an agonist of the trace amine-associated receptor 1 (TAAR1) (10).…”
mentioning
confidence: 99%
“…The combination of drug-and gene-based therapies enables simultaneous treatment of all key metabolic syndrome pathologies. Guanabenz (Wytensin) is a clinically licensed antihypertensive drug that is thought to activate alpha-2-selective adrenergic receptors in the central nervous system, thereby reducing the sympathetic outflow to heart, kidney, and peripheral vasculature and decreasing the systolic and diastolic blood pressure (9). Recently, guanabenz was also identified as an agonist of the trace amine-associated receptor 1 (TAAR1) (10).…”
mentioning
confidence: 99%
“…58,59 It has recently been reported that the morning/evening (M/E) or evening/ morning (E/M) ratio obtained from home BP measurements is very effective in evaluating the duration of drug effects. 57,58,60 3) HOME BP AND TELEMEDICINE With the advance of devices for home BP measurements, BP values have begun to be stored as electronic data. As a result, such data have been transmitted via telephone lines or the internet, and are widely used for decision making [61][62][63][64][65] and clinical pharmacological evaluations.…”
Section: ) Home Bp and Prognosismentioning
confidence: 99%
“…Evaluating the trough effect allows a definition of the duration of action of the drugs. 60 Recently, morning hypertension has been attracting attention, and some antihypertensive drugs are administered just after waking to control morning hypertension. In such cases, BP measurements before drug ingestion are recommended, although measurements 5-10 min after drug ingestion are also permitted.…”
Section: Before Taking Antihypertensive Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that treatment with sympatholytic drugs (eg, α-blockers, α, β-blockers, and central sympatholytic drugs) before bedtime is effective in the treatment of morning hypertension and morning surge. 54, 55 Bedtime administration of RA inhibitors is also used as a specific treatment of morning hypertension. It is expected that drugs inhibiting the RA system, which is activated at night and in the early morning, not only reduce blood pressure but also protect target organs.…”
Section: Morning Hypertensionmentioning
confidence: 99%